A influencia dos fluxos telefônicos na (re) organização urbana do Rio Grande do Sul - Marafon, Glaucio José; Becker, Elsbeth Léia Spode; Zillmer, Rafaela Janice (Geografia Ensino & Pesquisa, 2016)
A influencia dos fluxos telefônicos na (re) organização urbana do Rio Grande do Sul